Rate and reasons for elective ventilation in patients undergoing intracranial tumour surgery - Charu Mahajan; Girija Prasad Rath; Manish Singh Sharma; Surya Kumar Dube; Vanitha Rajagopalan; Parmod Kumar Bithal (Journal of Neuroanaesthesiology and Critical Care, 2014)
Background: Mechanical ventilation (MV) after neurosurgery is often decided by the preoperative neurological status of the patient. However, there is paucity of information regarding factors responsible for continuation of MV in these patients. This study was carried out to identify the indications and risk factors for elective ventilation after intracranial tumour surgery. Materials and Methods: A prospective observational study was carried out on consecutive adult patients who underwent elective craniotomy for tumour excision, and postoperatively required MV. Data on anaesthesia technique, duration of anaesthesia and surgery, blood loss and transfusion and volume of fluids infused were noted. Intraoperative complications like tight brain, massive blood loss, brainstem handling, cranial nerve handling, haemodynamic instability, cardiac arrhythmias, venous air embolism, electrolyte abnormality and hypothermia were also recorded. Statistical analysis was done using Strata 9.0 software. Categorical data was analysed using Chi-square test or Fisher's exact test and continuous data by Student's t-test. Results: A total of 709 patients enrolled for the study over a period of one year out of which 347 patients (48.9%) required continuation of MV during the postoperative period. The mean duration of MV was 29.7 ± 39.7 hrs. The most common causes for postoperative MV were ‘not responding to commands’ (43.2%), and neurosurgeon's advice (41.8%). The mean ICU and hospital stays were 92.2 ± 134.0 hrs and 13.8 ± 16.5 days, respectively. 47.6% of patients who required postoperative MV on neurosurgeon's advice developed complications whereas it was 33.2% for those ventilated other reasons (P < 0.05). Glasgow outcome scale (GOS) at discharge was poor in 12.4%. On multivariate analysis, intraoperative blood transfusion, tracheostomy and duration of ventilation more than 48 hrs were the independent risk factors associated with poor outcome. Conclusions: Although the neurosurgeon's advice for elective ventilation should not be ignored, but prolonged and avoidable MV may exacerbate the postoperative morbidities apart from increasing the cost of treatment. Hence, a complete understanding of intraoperative events, cerebral physiology and various factors influencing it during the perioperative period may not be overemphasised.